Quantitative Proteome Analysis Reveals Increased Content of Basement Membrane Proteins in Arteries From Patients With Type 2 Diabetes Mellitus and Lower Levels Among Metformin Users. (October 2015) - Preil, Simone A.R.; Kristensen, Lars P.; Beck, Hans C.; Jensen, Pia S.; Nielsen, Patricia S.; Steiniche, Torben; Bjørling-Poulsen, Marina; Larsen, Martin R.; Hansen, Maria L.; Rasmussen, Lars M.
Abstract : Background—: The increased risk of cardiovascular diseases in type 2 diabetes mellitus has been extensively documented, but the origins of the association remain largely unknown. We sought to determine changes in protein expressions in arterial tissue from patients with type 2 diabetes mellitus and moreover hypothesized that metformin intake influences the protein composition. Methods and Results—: We analyzed nonatherosclerotic repair arteries gathered at coronary bypass operations from 30 patients with type 2 diabetes mellitus and from 30 age- and sex-matched nondiabetic individuals. Quantitative proteome analysis was performed by isobaric tag for relative and absolute quantitation-labeling and liquid chromatography–mass spectrometry, tandem mass spectrometry analysis on individual arterial samples. The amounts of the basement membrane components, α1-type IV collagen and α2-type IV collagen, γ1-laminin and β2-laminin, were significantly increased in patients with diabetes mellitus. Moreover, the expressions of basement membrane components and other vascular proteins were significantly lower among metformin users when compared with nonusers. Patients treated with or without metformin had similar levels of hemoglobin A1c, cholesterol, and blood pressure. In addition, quantitative histomorphometry showed increased area fractions of collagen-stainable material in tunica intima and media among patients with diabetes mellitus. Conclusions—: The distinct accumulation of arterial basement membrane proteins in type 2 diabetes mellitus discloses a similarity between the diabetic macroangiopathy and microangiopathy and suggests a molecular explanation behind the alterations in vascular remodeling, biomechanical properties, and aneurysm formation described in diabetes mellitus. The lower amounts of basement membrane components in metformin-treated individuals are compatible with the hypothesis of direct beneficial drug effects on the matrix composition in the vasculature. Abstract : Supplemental Digital Content is available in the text.